2016
DOI: 10.3389/fpls.2016.01779
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Rice yellow mottle virus Polyprotein P2a Involved in RYMV2 Gene Resistance Breakdown

Abstract: Rice yellow mottle virus (RYMV) is one of the major diseases of rice in Africa. The high resistance of the Oryza glaberrima Tog7291 accession involves a null allele of the RYMV2 gene, whose ortholog in Arabidopsis, CPR5, is a transmembrane nucleoporin involved in effector-triggered immunity. To optimize field deployment of the RYMV2 gene and improve its durability, which is often a weak point in varietal resistance, we analyzed its efficiency toward RYMV isolates representing the genetic diversity of the virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 60 publications
2
42
0
Order By: Relevance
“…Several highly resistant varieties with known genes of resistant to RYMV have been identified that include rice cultivars Gigante (rymv1-2) [3], Tog12387 (rymv1-3) [6], Tog5681 (rymv1-3) [4], Tog5438 (rymv1.4), Tog5672 (rymv1-4+rymv2) and Tog5674 (rymv1-5) [7]. Resistance conferred by RYMV2 and RYMV3 genes have currently been identified on Oryza glaberrima Tog7291 and Tog5307, respectively [2] [8]. Partial genetic resistance quantitative trait locus (QTLs) which is polygenic has been reported to be widespread in Oryza sativa subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Several highly resistant varieties with known genes of resistant to RYMV have been identified that include rice cultivars Gigante (rymv1-2) [3], Tog12387 (rymv1-3) [6], Tog5681 (rymv1-3) [4], Tog5438 (rymv1.4), Tog5672 (rymv1-4+rymv2) and Tog5674 (rymv1-5) [7]. Resistance conferred by RYMV2 and RYMV3 genes have currently been identified on Oryza glaberrima Tog7291 and Tog5307, respectively [2] [8]. Partial genetic resistance quantitative trait locus (QTLs) which is polygenic has been reported to be widespread in Oryza sativa subsp.…”
Section: Introductionmentioning
confidence: 99%
“…In West-Central Africa, we identified that the hypervirulent pathotype T9 is able to overcome all of the resistance alleles of RYMV1, even the most efficient ones, rymv1-3 and rymv1-5. Isolates of this pathotype are able to infect sources of resistance carrying the RYMV2 and RYMV3 resistance alleles (Pidon et al 2017;Pinel-Galzi et al 2016). Preliminary results also suggested resistance breakdown of the Tog5672 accession (carrying both rymv1-4 and RYMV2).…”
Section: Discussionmentioning
confidence: 59%
“…In our study, we assessed the first step of the viral adaptation to resistant accessions (i.e., the qualitative ability to overcome resistance). Different isolates that are able to overcome Tog7291 (RYMV2) show high or very low frequencies of RB events (Pinel-Galzi et al 2016). In future studies, measures of variability and frequency should be performed to quantify and predict the RB risks in real conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, the CPR5 nucleoporin gene is involved in the regulation of defense mechanisms and senescence [15,16]. Considering the sequence homology and in line with previous studies [13,17], the candidate gene for RYMV2 is hereafter referred to as CPR5-1, although its nucleoporin role and involvement in defense mechanisms has yet to be documented in rice. More recently, a gene of the nucleotide binding domain and leucine-rich repeat gene (NLR) superfamily was pinpointed as the best candidate for the RYMV3 dominant resistance gene [18].…”
mentioning
confidence: 95%